Analisis Hubungan antara Usia dengan Tingkat Kelelahan Kerja Pekerja Departemen Produksi Perusahaan Pipa Baja di Surabaya - Fauziyyah Nabilah (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to determine the relationship between age and work fatigue levels among workers in the Production Department of a steel pipe company in Surabaya. The research design is quantitative with a cross-sectional approach, involving the entire population of workers, with a total of 55 workers as samples using total sampling technique. The dependent variable in this study is work fatigue, and the independent variable is age. Work fatigue level data was measured using a reaction timer, and age data was collected through respondent data sheets. The analysis was conducted using Spearman's test with α = 0.05 using SPSS. The results showed that age and work fatigue levels had a significant relationship (p= <0.001) with a very strong correlation coefficient (r = 0.826). This study suggests that companies pay attention to the factors that cause work fatigue among their workers through regulating working hours and providing brief socialization on fatigue awareness.